Reflective Approach in Training Counselors at University - Alena V. Kibalnik, Tatyana F. Usheva, Irina V. Fedosova, Inna V. Berinskaya, Olga V. Gordina, (Opción, 2019)
The aim of the study is to investigate the reflective approach in training counselors at university via the method of determining cooperative introspection. As a result, comparison of the level of formation of intellectual reflection in the experimental and control groups showed a positive dynamics towards the experimental group. In conclusion, learning through reflective approach involves the creation of certain pedagogical conditions in a university that contribute to student's awareness of being a free and responsible person seeking self-improvement and self-realization in order to implement the tasks of humanization of education